2008
DOI: 10.1111/j.1526-4637.2007.00353.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiological Anatomy of the Obturator Nerve and Its Articular Branches: Basis to Develop a Method of Radiofrequency Denervation for Hip Joint Pain

Abstract: The method that we described has the potential to produce complete and reliable nerve coagulation. Moreover, it minimizes the risk of penetrating the great vessels. The efficacy of this approach should be tested in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
59
0
6

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 21 publications
1
59
0
6
Order By: Relevance
“…6,[8][9][10][12][13][14][24][25][26][27][28][29] Our findings are similar to those described by Locher et al, 26 who detailed the anatomic course of articular branches of the ON and their relationship to bony landmarks. They described articular branches located lateral to the obturator foramen, just below the acetabulum.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…6,[8][9][10][12][13][14][24][25][26][27][28][29] Our findings are similar to those described by Locher et al, 26 who detailed the anatomic course of articular branches of the ON and their relationship to bony landmarks. They described articular branches located lateral to the obturator foramen, just below the acetabulum.…”
Section: Discussionsupporting
confidence: 82%
“…The radiographic targets for branches of the FN were either the superolateral acetabular margin or the AIIS. While the anatomic relationship between the radiographic target and the neural innervation from ON has been examined, 26 the relationship between FN and AON articular branches to the bony landmarks remains unconfirmed. The anatomic course of ON branches in this study was consistent with previously reported findings.…”
Section: Discussionmentioning
confidence: 99%
“…Analgesia for proximal femur fractures may be obtained by blocking the femoral nerve, whether via a single injection or continuous block technique. Although the femur has innervations from multiple nerves, proximally, the femur is predominantly innervated by the femoral nerve, with contributions from the sciatic nerve and an articular branch of the obturator nerve [Locher et al, 2008].…”
Section: Femur Fracturesmentioning
confidence: 99%
“…With a final return to AP fluoroscopic imaging, the needle is adjusted into final lesioning positioning across the ischium. 18 Locher recognized that the utility of placing the maximum needle electrode on the ischial surface required an extremely lateral entry angle. This author has reviewed 40 pelvic magnetic resonance imagings to determine the minimum angle of incidence and needle passage required to avoid the femoral neurovascular bundle, modifying Locher's original technique for use with a cooled RF probe to use a combined 501 oblique and 201 declined fluoroscopic technique with subsequent final RF probe adjustment in the AP projection.…”
mentioning
confidence: 99%
“…For the hip joint, the anterior capsular innervation is provided by the femoral articular nerve(s) and the obturator articular nerve, 17,18 both of which pass through bony notches to enter the joint capsule. Both of these nerves are amenable to RFL.…”
mentioning
confidence: 99%